2005
DOI: 10.1177/003335490512000108
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Factors and the Risk of Anencephaly in a Mexican Population: A Case-Control Study

Abstract: Objective. The study was designed to evaluate the association between socioeconomic level (as measured by maternal education, maternal occupation, and monthly family income) and anencephaly. Methods. The authors conducted a case-control study using data from the Epidemiological Surveillance System Register for Neural Tube Defects for three states of the Mexican Republic: Puebla, Guerrero and the State of Mexico. Mothers of 151 cases of infants born with anencephaly and mothers of 151 control infants born durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 24 publications
1
6
1
Order By: Relevance
“…Our finding of an association between low levels of maternal education and an increased risk of NTDs is consistent with the conclusions of Wasserman et al 9 . Their results have been substantiated by several subsequent studies, where the reported risk estimates for NTDs ranged between 1.8 and 2.3 for mothers with less than a high school education 4,5,10 . These findings, however, diverge from the conclusions of two other studies that observed no association between risk of NTDs and educational level of the mother 11,12 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our finding of an association between low levels of maternal education and an increased risk of NTDs is consistent with the conclusions of Wasserman et al 9 . Their results have been substantiated by several subsequent studies, where the reported risk estimates for NTDs ranged between 1.8 and 2.3 for mothers with less than a high school education 4,5,10 . These findings, however, diverge from the conclusions of two other studies that observed no association between risk of NTDs and educational level of the mother 11,12 …”
Section: Discussionsupporting
confidence: 90%
“…Two of the other studies were conducted in Colorado 10 and Texas, 20 respectively, and limited their study population to Hispanic women who were born either in the US or Mexico, in all cases prior to fortification. Two further studies focused on women who resided in Mexico 4 and Spain 12 respectively. In addition, the studies did not derive the samples of infants with malformations in an equivalent manner – one included all liveborn, stillborn and electively terminated cases with NTDs, 9 another used livebirths and stillbirths, 20 and a third used only livebirths 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding goes in concordance with other studies where increased incidences of NTD's have been found in families of low SES. Blanco Muñoz et al .,[ 4 ] in their study, in a Mexican population found increased risk of anencephaly in mothers of low SES. Mutchinick et al .…”
Section: Discussionmentioning
confidence: 93%
“…Blanco Muñoz et al . [26] in their study in a Mexican population found increased risk of anencephaly in mothers of low SES. Mutchinik et al .…”
Section: Discussionmentioning
confidence: 97%